2009
DOI: 10.4103/0973-8398.56302
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, characterization andin vitroevaluation of floating microspheres of famotidine as a gastro retentive dosage form

Abstract: T he present study involves preparation and evaluation of floating microspheres using famotidine (FM) as a model drug for prolongation of the gastric retention time. The microspheres were prepared by the solvent evaporation method using different polymers, i.e. acrycoat S100 and cellulose acetate. The size or average diameter (d avg ) and surface morphology of the prepared microspheres were recognized and characterized by the optical and scanning electron microscopic methods, respectively. In vitro drug releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Quantitative determination of nizatidine hydrochloride was carried out after suitable dilution using UV/Visible spectrophotometer (Shimadzu 1800, Japan). The experiment was repeated with the different volume of the solvents to obtain more appropriate degree of solubility [16,17]. The profi le of solubility of nizatidine HcL in different solvent is given in Table 1.…”
Section: Solubility Profi Lementioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative determination of nizatidine hydrochloride was carried out after suitable dilution using UV/Visible spectrophotometer (Shimadzu 1800, Japan). The experiment was repeated with the different volume of the solvents to obtain more appropriate degree of solubility [16,17]. The profi le of solubility of nizatidine HcL in different solvent is given in Table 1.…”
Section: Solubility Profi Lementioning
confidence: 99%
“…base to adhere the balloons for increase the retarding of drug release, thus will be effective for drug delivery through oral mucosa for peptic ulcer management [13][14][15]. profi le in various aqueous and nonaqueous solvents, partition coeffi cient and FTIR study [16,17].…”
mentioning
confidence: 99%
“…All the six formulation of Levofloxacin microspheres were tested for stability studies in stability chamber. Formulation was exposed up to 30 and 60 days of stability studies at 40°C ± 2°C and 75% ± 5% RH [13][14] . 1085…”
Section: Stability Studiesmentioning
confidence: 99%
“…Materials used for FDDS include carbon dioxide gas-forming agents (carbonate or bicarbonate compounds) 8,13 , highly swellable hydrocolloids and light mineral oils 14,15 . Multiple unit systems and floating systems prepared by solvent evaporation methods have also been developed 12,[16][17][18][19][20] . However, it has been shown that products based on a multiple unit system comprising many small units have advantages over single -unit preparations such as matrix tablets 21 .…”
Section: Introductionmentioning
confidence: 99%